In Vitro Activities of Antimicrobials Against Toxigenic Clostridioides difficile Isolates Obtained in a University Training and Research Hospital in Turkey - BİLGİN, HÜSEYİN; ÜLGER, NURVER (ANKARA MICROBIOLOGY SOC, 2020)
Clostridioides difficile, a gram-positive, anaerobic, spore forming bacillus known as Clostridium difficile according to the previous taxonomy, is the most important agent of antibiotic-associated diarrhea. C.difficile infections have become a major health problem for many countries. The rate of antimicrobial resistant C.difficile isolates is rapidly increasing all around the world. Yet there is limited data on this subject in our country. The aim of this study was to determine the antimicrobial susceptibility profiles of C.difficile strains isolated from stool samples in Marmara University Pendik Training and Research Hospital Microbiology Laboratory. A total of 93 toxigenic C.difficile, defined by serological and molecular techniques, were included in this study. Antimicrobial susceptibility profiles of isolates were determined by using agar dilution method according to the Clinical and Laboratory Standards Institute (CLSI; M11-A7). The following antimicrobials commonly used for the treatment of C.difficile infections or applied previously in C.difficile epidemiological studies were tested: metronidazole, vancomycin, meropenem, ceftriaxone, ampicillin-sulbactam, clindamycin, erythromycin, moxifloxacin, tetracycline, doxycycline, tigecycline and linezolid. The minimum inhibitory concentration (MIC) results were interpreted according to the breakpoints described by the European Committee on Antimicrobial Susceptibility Testing (EUCAST). Breakpoints recommended by CLSI were applied for ceftriaxone, clindamycin, tetracycline and moxifloxacin since there were no EUCAST breakpoints for these antimicrobials. MIC50 and MIC90 values were determined for three antimicrobials (linezolid, erythromycin, doxycycline) whose breakpoints were not described by EUCAST or CLSI guidelines. All isolates were susceptible to metronidazole, vancomycin, ampicillin-sulbactam, meropenem and tetracycline. Susceptibility to ceftriaxone, clindamycin and moxifloxacin was found in 58.1%, 35.5% and 20.4% of the isolates, respectively. MIC50 and MIC90 values of tigecycline, erythromycin linezolid, doxycycline were 0.125-0.25 mg/L, 1-2 mg/L, 2-2 mg/L, 0.0620.125 mg/L, respectively. This study shows the current antimicrobial susceptibility patterns of C.difficile isolates in our hospital and will also be the reference data for clinical laboratories in our country where anaerobic culture and susceptibility tests are not performed in routine practice. In conclusion, two main antimicrobial agents commonly used in the treatment of C.difficile infections, metronidazole and vancomycin, seem to be effective. However, high resistance rates against to the certain tested antimicrobials highlight the need for further surveillance to monitor the emergence of resistance.
Keywords: Clostridioides difficile; antimicrobial susceptibility; metronidazole; vancomycin; MOLECULAR EPIDEMIOLOGY; ANTIBIOTIC-RESISTANCE; SUSCEPTIBILITY; STRAINS